علم المعاني: تعريفه، ونشأته، وأنواعه - Elok Rufaiqoh (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
The research aims to know the definition of the science of meanings, its origins, and its types. The approach used in this research is a qualitative descriptive approach, and the type of research is a desk study with content analysis. As for the results of the research, they are: (1) The science of meanings is the foundations and rules, by which the conditions of Arabic speech are known by which they are in conformity with the requirements of the situation, so that they are in accordance with the purpose for which they were conceived. (2) Abd al-Qaher al-Jurjani developed the theory of the science of meanings in the fifth century AH, i.e. the year 471 AH, and it is strange that no explanation occurred after him mentioning in these two sciences “the science of meanings and the statement” because he was able to derive from the observations of the rhetoricians before him all the rhetorical rules in it, and that was a signal To turn those rules after him into rigid laws, as if the research in rhetoric had ended with Abd al-Qahr al-Jurjani (3) The types of semantics are eight, namely: predicate, creation, predicate and predicate, verb related, shortening, separation and connection, brevity, and redundancy , and equality. Keywords: The science of meanings, Developtment, and Types